OBESITY AND DIABETES MELLITUS AS PREDICTORS OF MORTALITY IN PATIENTS WITH STROKE: A META ANALYSIS - Karlinda, Karlinda; Tamtomo, Didik Gunawan; Murti, Bhisma (Indonesian Journal of Medicine, 2019)
Background: Stroke is the leading cause of death and disability throughout the world. Based on studies in the United States (US), a person experiences a stroke every 40 seconds and every 4 minutes someone dies. The problem of comorbidity or the presence of more than one disease is the risk of stroke. This causes a person with comorbidities to have a higher risk of mortality than stroke patients without comorbidities. This study aims to examine the effect of obesity and diabetes mellitus as predictors of mortality in stroke patients.Subjects and Method: This was a meta-analysis and systematic review. The articles were obtained from Google Scholar, PubMed, Springer Link, Clinical key, and ProQuest databases. The articles have been published from 2010-2019. Keywords to search for articles are as follows: "comorbidity and stroke", "comorbidity and mortality and stroke and cross sectional study", "comorbidity and mortality and stroke and adjusted odd ratio", "comorbidity or stroke", "comorbidity or mortality or stroke or cross sectional study ", "comorbidity or mortality or stroke or adjusted odd ratio". The articles studied are full text articles with observational study design. Articles are collected using PRISMA diagram, and analyzed using the Review Manager application 5.3.Results: Obesity (aOR = 1.51; 95% CI = 1.03 to 2.21; p = 0.030) and diabetes mellitus (aOR = 1.75; 95% CI = 1.33 to 2.29; p <0.001) are predictors of mortality in stroke patients.Conclusion: Obesity and diabetes mellitus are predictors of mortality in stroke patients.Keywords: obesity, diabetes mellitus, strokeCorrespondence: Karlinda. Masters Program in Public Health Sciences, Universitas Sebelas Maret, Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: karlindalinda8@gmail.com. Mobile: +6282278924093Indonesian Journal of Medicine (2019), 4(4): 383-393https://doi.org/10.26911/theijmed.2019.04.04.12